Long-term effect of neoadjuvant denosumab treatment in high-risk early breast cancer (GeparX) - Link, Theresa; Reinisch, Mattea; Just, M.; Untch, M.; Filmann, N.; Stötzer, O.; Denkert, C.; Bjelic-Radisic, V.; Wimberger, P.; Thill, M.; Rhiem, K.; Huober, J.; et al. (ESMO open, 2025)
Background - In the GeparX trial (NCT02682693), neoadjuvant denosumab, in addition to either weekly or days 1 and 8 (d1,8) q22 nab-paclitaxel (nPac)-based chemotherapy, did not improve the pathological complete response (pCR) rate in early high-risk breast cancer patients, while the concomitantly applied weekly nPac regimen resulted in a significantly higher pCR rate compared with the interrupted regimen. - Patients and methods - GeparX is a randomized, open-label, phase II study comparing neoadjuvant treatment with or without denosumab and two different nPac schedules. Invasive disease-free survival (iDFS), distant disease-free survival (DDFS), overall survival (OS), and locoregional recurrence-free interval (LRRFI) were considered as time-to-event endpoints. - Results - After a median follow-up of 62.3 months, there was no statistically significant difference in iDFS [hazard ratio (HR) 0.86, 95% confidence interval (CI) 0.62-1.21, P = 0.39], DDFS (HR 0.77, 95% CI 0.54-1.11, P = 0.16), LRRFI (HR 1.41, 95% CI 0.76-2.63, P = 0.28), and OS (HR 0.81, 95% CI 0.50-1.33, P = 0.41) between denosumab-treated and non-denosumab-treated patients. However, numerically fewer distant relapses occurred in patients with denosumab treatment (9.2% versus 13.8%). Denosumab treatment resulted in a significant risk reduction of 36% for distant relapse in the multivariate analysis (DDFS; HR 0.64, 95% CI 0.43-0.93, P = 0.02). There was no overall differential impact of the two neoadjuvant chemotherapy (NACT) regimens (nPac weekly or nPac d1,8 q22) on long-term outcome in the total study population. Triple-negative breast cancer (TNBC) patients without a pCR (non-pCR) had a significantly worse iDFS (HR 0.22, 95% CI 0.12-0.39, P < 0.0001), with a trend toward improved iDFS in those receiving weekly nPac at the 5-year landmark (iDFS rate at 60 months: 58.4% versus 72%). - Conclusions - Denosumab as part of neoadjuvant therapy, although not improving the pCR rate, significantly reduced the risk of distant relapses. Other long-term outcome parameters did not differ between the treatment arms. TNBC patients, especially when not achieving pCR, seem to benefit from weekly nPac.
Online verfügbar: 27. November 2025, Artikelversion: 27. November 2025
Gesehen am 17.02.2026